REVIEW OF KHURSHID AHMAD'S THOUGHTS ON ISLAMIC ECONOMIC DEVELOPMENT - Hamzani, Achmad Irwan; Soeharto, Achmad; Taufiq, Taufiq; Khasanah, Nur; Aravik, Havis (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2025)
The purpose of this study is to examine Khurshid Ahmad's Islamic economic thought, the philosophical foundations that were built, and the idea of ​​Islamic economic development. This research is a type of library research, using secondary data, and a philosophical approach by looking at Khurshid Ahmad's idea as an ideal. The findings according to Khurshid, the existence of Islamic economy is different from conventional economy, both in the form of capitalist and socialist. The essence of Islamic economics is the application of sharia in economic activity. Economic philosophy is built and embodied the content of the Qur'an and al-Hadith. Islamic economic philosophy is based on the concept of a triangle: namely the philosophy of God, man and nature. Economic development is a multidimensional activity so that all efforts must be left to the balance of various factors and not create inequality. The ultimate goal of Islamic development is the welfare of mankind through the integration of social norms, ethical values, economics and politics. The value of the Study Khurshid's ideas on Islamic economic development have not been widely studied. With this research, Khurshid's idea can be studied that Islamic economics is a unique and distinctive economic concept and system, guided by Islamic teachings. As a system of life, Islamic teachings will not be optimally present as a map of life if they are not supported by economic sub-systems. The ultimate goal of Islamic development is the welfare of the world and the hereafter.